Role of Social Media Literacy in Improving the Cybersecurity Measures: A Case Study in India (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In the modern world social media literacy plays a significant role in enhancing cybersecurity measures specifically in India. Background information regarding the research topic has been discussed effectively along with highlighting the aim, objectives along with research questions that reflect as a foundation of the research. Besides this, lack of digital literacy in rural and urban areas of India has been discussed as an issue. In-depth literature review along with thematic implications such as “Protection Motivation Theory (PMT)” and “Theory of Planned Behaviour (TPB)” has also been illustrated in this research. Furthermore, the selection of “secondary data collection method” along with expected outcome has also been discussed in this report.